Non-obstetric traumatic vulval hematoma in a teenage girl - Pandit, Mahima; Hansda, Rosalin; Mondal, Prasanta Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Few occurrences of non-obstetric vulvar haematomas have been documented in the literature, making them uncommon. For their treatment, there are no clinical recommendations. Most of the time, they can be managed conservatively, but occasionally, surgery will be required. We describe the surgically treated patient who had a traumatic vulvar haematoma.